The risks of the new morbidities acquired during pediatric onco-critical care and their life-shortening effects - Gabriela Maria Virgílio Dias Santos; Orlei Ribeiro de Araujo; Priscila de Biasi Leal; Rodrigo Genaro Arduini; Rosa Massa Kikuchi de Sousa; Eliana Maria Monteiro Caran; Dafne Cardoso Bourguignon da Silva (Elsevier, 2023)
Objective: The authors investigated the functional status at ICU admission and at hospital discharge, and the impact of dysfunctions on survivors' lifespan. Method: Single-center retrospective cohort. The FSS (Functional Status Scale) was calculated at ICU admission and at hospital discharge. A new morbidity was defined as an increase in FSS ≥ 3. Results: Among 1002 patients, there were 855 survivors. Of these, 194 (22.6%) had died by the end of the study; 45 (5.3%) had a new morbidity. Means in the motor domain at admission and discharge were 1.37 (SD: 0.82) and 1.53 (SD 0.95, p = 0.002). In the feeding domain, the means were 1.19 (SD 0.63) and 1.30 (SD 0.76), p = 0.002; global means were 6.93 (SD 2.45) and 7.2 (SD 2.94), p = 0.007.  Acute respiratory failure requiring mechanical ventilation, the score PRISM IV, age < 5 years, and central nervous system tumors were independent predictors of new morbidity. New morbidity correlated with lower odds of survival after hospital discharge, considering all causes of death (p = 0.014), and was independently predictive of death (Cox hazard ratio = 1.98). In Weibull models, shortening in the life span of 14.2% (p = 0.014) was estimated as a new morbidity. Conclusions: New morbidities are related to age, disease severity at admission, and SNC tumors. New morbidities, in turn, correlate with lower probabilities of survival and shortening of the remaining life span. Physical rehabilitation interventions in this population of children may have the potential to provide an increase in lifespan.